Pfam: The protein families database in 2021. Issue Volume 49:Issue D1(2021) (30th October 2020) - Mistry, Jaina; Chuguransky, Sara; Williams, Lowri; Qureshi, Matloob; Salazar, Gustavo A; Sonnhammer, Erik L L; Tosatto, Silvio C E; Paladin, Lisanna; Raj, Shriya; Richardson, Lorna J; Finn, Robert D; Bateman, Alex
Abstract: The Pfam database is a widely used resource for classifying protein sequences into families and domains. Since Pfam was last described in this journal, over 350 new families have been added in Pfam 33.1 and numerous improvements have been made to existing entries. To facilitate research on COVID-19, we have revised the Pfam entries that cover the SARS-CoV-2 proteome, and built new entries for regions that were not covered by Pfam. We have reintroduced Pfam-B which provides an automatically generated supplement to Pfam and contains 136 730 novel clusters of sequences that are not yet matched by a Pfam family. The new Pfam-B is based on a clustering by the MMseqs2 software. We have compared all of the regions in the RepeatsDB to those in Pfam and have started to use the results to build and refine Pfam repeat families. Pfam is freely available for browsing and download at http://pfam.xfam.org/ .